PEMANFAATAN MEDIA PEMBELAJARAN KAHOOT BERBASIS HYPERMEDIA PADA PELAJARAN MATEMATIKA KELAS V DI SDN 1 KELAYU UTARA - Niswatul Fitriani; Muhammmad Sururuddin; Husnul Mukti; Doni Septu Marsa Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem in this study is the low mathematics learning outcomes of fifth-grade students caused by conventional learning methods and the lack of interactive media utilization among Phase C students at SDN 1 Kelayu Utara. This study aims to determine the effect of using Kahoot-based hypermedia learning media on the mathematics learning outcomes of Phase C students at SDN 1 Kelayu Utara. The research employed an experimental method with a one-group pretest–post-test design. The sample consisted of all 26 fifth-grade students at SDN 1 Kelayu Utara. Data were collected by administering pretests and post-tests in the form of multiple-choice questions. Data analysis was conducted using a normality test with the Lilliefors method and a hypothesis test using a t-test. The results showed that the pretest scores ranged from 30 to 75 with an average of 57.2, while the post-test scores ranged from 50 to 85 with an average of 69.4. Based on the normality test results, the pretest data showed that lcalculated < ltable (0.177 < 0.220), and the post-test data showed that lcalculated < ltable (0.198 < 0.220), indicating that the data were normally distributed. Furthermore, the hypothesis test results showed that tcalculated > ttable (6.982 > 2.120), meaning that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Therefore, it can be concluded that the use of Kahoot-based hypermedia learning media has a significant effect on improving the mathematics learning outcomes of fifth-grade students at SDN 1 Kelayu Utara.